Teacher Participation in Academic Administration in Schools under the Secondary Educational Service Area Office of Chonburi Rayong, Rayong 2 School Consortium - ศรีสมบูรณ์, ธีรพล; การีเวท, สมนึก (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) investigate the level of teacher participation in academic administration in schools; 2) compare teacher participation in academic administration as classified by educational qualification, work experience, and school size; and 3) study guidelines for developing teacher participation in academic administration within the Rayong 2 Inter-school Cluster, under the jurisdiction of the Chonburi Rayong Secondary Educational Service Area Office. The sample, obtained through stratified random sampling, consisted of 209 teachers working during the 2025 academic year. The research instrument was a 5-point rating scale questionnaire with a total reliability of 0.978. Statistics used for data analysis included percentage, mean, standard deviation, and One-Way Analysis of Variance (One-Way ANOVA).            The findings revealed that: 1) The overall level of teacher participation in academic administration was at the highest level (x̄= 4.53, S.D. = 0.64). When considering individual aspects, participation was at the highest level in nearly all areas, with "learning process development" receiving the highest mean score, followed by "development and promotion of learning resources." The aspect of "development of internal quality assurance systems and educational standards" had the lowest mean score. 2) The comparison of teacher participation showed no significant overall differences when classified by educational qualification and work experience. However, a statistically significant difference was found at the .05 level when classified by school size. 3) Guidelines for developing teacher participation in academic administration focus on an approach driven by digital technology integrated with organizational culture. This emphasizes fostering ownership of learning, utilizing a central database (Big Data) to reduce workload, promoting a research culture, adapting supervision to a collegial model, and establishing a development plan for digital media production skills.